Digital image correlation for surface deformation measurement: historical developments, recent advances and future goals - Pan, Bing (Measurement science & technology, 2018)
This article is a personal review of the historical developments of digital image correlation (DIC) techniques, together with recent important advances and future goals. The historical developments of DIC techniques over the past 35 years are divided into a foundation-laying phase (1982-1999) and a boom phase (2000 to the present), and are traced by describing some of the milestones that have enabled new and/or better DIC measurements to be made. Important advances made to DIC since 2010 are reviewed, with an emphasis on new insights into the 2D-DIC system, new improvements to the correlation algorithm, and new developments in stereo-DIC systems. A summary of the current state-of-the-art DIC techniques is provided. Some further improvements that are needed and the future goals in the field are also envisioned.